Guidance for the use and reporting of anaesthetic agents in BJP manuscripts involving work with animals. (18th December 2022) - Ingrande, Jerry; Patel, Hemal H.; Kendall, Dave; Stefanska, Barbara; Alexander, Steve; Bakhle, Mick; Cirino, Giuseppe; Docherty, James R.; George, Christopher H.; Insel, Paul A.; Ji, Yong; King, Brian F.; et al.
Abstract : Scientists who plan to publish in the British Journal of Pharmacology ( BJP ) should read this article before undertaking studies utilising anaesthetics in mammalian animals. This editorial identifies certain gaps in the reporting of details on the use of anaesthetics in animal research studies published in the BJP . The editorial also provides guidance, based upon current best practices, for performing in vivo experiments that require anaesthesia. In addition, mechanisms of action and physiological impact of specific anaesthetic agents are discussed. Our goal is to identify best practices and to provide guidance on the information required for manuscripts submitted to the BJP that involve the use of anaesthetic agents in studies with experimental animals.